Social Media Is A Moderating Variables of purchasing Decisions - Anah Furyanah; Pramono Hari Adi; Haidilia Maharani (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
This study analyzes the effect of price, promotion, and social media on purchasing decisions and analyzes social media to moderate price and promotion variables. A quantitative approach using a questionnaire tested with validity and reliability by using SPSS 2.6 using regression and Moderated Regression Analysis (MRA) to determine the ability to analyze between variables. This research was conducted on coffee businesses that had just entered the coffee market and were influenced by various factors. In this study, price and promotion have a significant effect on purchasing decisions. Meanwhile, social media has no significant effect on purchasing decisions. Therefore, social media is unable to moderate prices and promotions on purchasing decisions. With the results of this study, the Cilumping Robusta Basma coffee business must take advantage of the benefits in increasing sales. It is carried out on a coffee product business that is starting to develop, and there has never been an analysis of price and promotion, so the author wants to know what factors can encourage consumers to make purchasing decisions.